PCR detection of cytomegalovirus DNA in serum as a diagnostic test for congenital cytomegalovirus infection. - Nelson, C T (1995)
PCR detected cytomegalovirus (CMV) DNA in the serum of 18 of 18 infants with symptomatic congenital CMV infection, 1 of 2 infants with asymptomatic congenital CMV infection, and 0 of 32 controls. Serum CMV PCR provided a rapid, sensitive, and specific method for diagnosis of congenital CMV infection in infants who were symptomatic at birth.